PUBLIC RELATIONS COMMUNICATION STRATEGY OF PTPN 4 REGIONAL 1 MEDAN DALAM (CORPORATE SOCIAL RESPONSIBILITY) IN SOCIAL AND RELIGIOUS EDUCATION - Rifqi Adriansa Yoes; Zuhriah Zuhriah (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to analyze the public relations communication strategy of PTPN IV Regional 1 Medan in implementing Corporate Social Responsibility (CSR) programs in the fields of education, social welfare, and religion. The study also examines community responses to CSR communication and the obstacles faced by the Public Relations team in delivering CSR information to beneficiaries. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation involving public relations officers, company management, and community members who received CSR program benefits. The findings show that the CSR communication strategy implemented by PTPN IV Regional 1 received positive responses from the community. The messages delivered by the Public Relations team were considered clear, simple, and understandable because they explained the objectives, forms of assistance, target beneficiaries, and benefits of the CSR programs. Face-to-face communication was found to be the most effective channel, supported by social media, online publications, and activity documentation. The strategy also encouraged community participation, increased public trust, and strengthened the company’s positive image. However, several obstacles were identified, including uneven information distribution, differences in public understanding, limited digital access, low digital literacy, and internal coordination challenges. Overall, the study confirms that effective CSR communication requires clear messages, appropriate media selection, credible communicators, and participatory engagement with the community.